Murder in Mexico: are journalists victims of general violence or targeted political violence?. Issue 7 (3rd October 2018) - Bartman, Jos Midas
ABSTRACT: Journalists in Mexico face hundreds of attacks each year, ranging from online harassment and physical intimidation to outright murder. The official narrative typically claims that murdered journalists are the victims of general criminal violence. This article finds that despite the rampant violence in Mexico, the murder of journalists cannot be attributed to the country's general criminal violence problem alone. Instead, the evidence points to the targeting, and even political targeting of journalists. First, journalists are at a much higher risk of being murdered than the general population. Second, the divergence between homicide rates among the general population and among journalists varies considerably between Mexican states. While recent scholarship has shown that subnational governments can successfully remain authoritarian despite democratization at the central or federal level, this literature has largely ignored the use of political killings in subnational undemocratic regimes. This article attempts to understand the murder of journalists not just as a problem of criminal violence, but also of political violence, and thereby connects the findings to the existing scholarship on subnational authoritarianism.